2023
DOI: 10.3389/fmars.2023.1184421
|View full text |Cite
|
Sign up to set email alerts
|

Increasing eutrophication driven by the increase of phosphate discharge in a subtropical bay in the past 30 years

Abstract: Although great efforts have been made to decrease nutrient (notably nitrogen and phosphorus) loads and lighten related environmental damages, coastal eutrophication remains a persistent environmental crisis. To estimate whether the rapid development of the local economy has accelerated the eutrophication in Zhanjiang Bay, a newly developing industry in South China, the combination of the seasonal nutrients and other physicochemical parameters from twenty cruises during 2017-2021 and historical data (past 30 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Compared to the Typhoon Barijat period (an average of 45.2 mmol L -1 for DIN) (Lao et al, 2023c), the stronger ocean front induced by the Typhoon Talim resulted in a significant increase in DIN concentration in the upper bay (increased by nearly 50%). This is mainly because runoff is the main DIN source in the bay, and the DIN input exhibited an increasing trend in the recent five years (2017-2021) (He et al, 2023). On the contrary, the input of PO 4 3decreased during this period (He et al, 2023), and thus less change of PO 4 3contribution was observed after the Typhoon Talim compared to the Typhoon Barijat (an average of 3.5 mmol L -1 in the upper bay).…”
Section: The Eco-environmental Effects Of Ocean Fronts Induced the Ty...mentioning
confidence: 96%
See 3 more Smart Citations
“…Compared to the Typhoon Barijat period (an average of 45.2 mmol L -1 for DIN) (Lao et al, 2023c), the stronger ocean front induced by the Typhoon Talim resulted in a significant increase in DIN concentration in the upper bay (increased by nearly 50%). This is mainly because runoff is the main DIN source in the bay, and the DIN input exhibited an increasing trend in the recent five years (2017-2021) (He et al, 2023). On the contrary, the input of PO 4 3decreased during this period (He et al, 2023), and thus less change of PO 4 3contribution was observed after the Typhoon Talim compared to the Typhoon Barijat (an average of 3.5 mmol L -1 in the upper bay).…”
Section: The Eco-environmental Effects Of Ocean Fronts Induced the Ty...mentioning
confidence: 96%
“…This is mainly because runoff is the main DIN source in the bay, and the DIN input exhibited an increasing trend in the recent five years (2017-2021) (He et al, 2023). On the contrary, the input of PO 4 3decreased during this period (He et al, 2023), and thus less change of PO 4 3contribution was observed after the Typhoon Talim compared to the Typhoon Barijat (an average of 3.5 mmol L -1 in the upper bay). However, in the lower bay, the DIN concentration during the posttyphoon Talim decreased compared to the Typhon Barijat (an average of 11.8 mmol L -1 ) (Lao et al, 2023c), mainly influenced by more seawater intrusion after stronger typhoon Talim.…”
Section: The Eco-environmental Effects Of Ocean Fronts Induced the Ty...mentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, excessive nutrient levels may cause significant phytoplankton blooms and high primary productivity, resulting in eutrophication, red tides, algal blooms, water hypoxia, and acidification (Wang et al, 2021a;Zhang et al, 2023aZhang et al, , 2023b. These factors can degrade the affected environments, directly threaten biodiversity and habitats, and cause massive mortality of marine organisms, ultimately harming marine ecosystems and human society (Deegan et al, 2012;Mauŕe et al, 2021;He et al, 2023).…”
Section: Introductionmentioning
confidence: 99%